To Boost Students' Motivation and Achievement through Blended Learning - Islam, Syaiful; Baharun, Hasan; Muali, Chusnul; Ghufron, Moh. Idil; Bali, Mushfi el Iq; Wijaya, Mualim; Marzuki, Ismail (Journal of physics. Conference series, 2018)
This study aims to determine differences in motivation and student achievement between students using direct learning model and students using blended learning model, improving motivation and student achievement by applying blended learning model of students of SMKN 1 Kraksaan. The quasi-experimental study used two groups, the experimental group using blended learning model and control group using direct learning model. The population of this research is the students of Eleven Grader of SMKN 1 Kraksaan. The result of the research shows that there is a significant difference between students 'motivation and achievement using blended learning model and students using direct learning model, there is a significant increase of students' motivation and achievement as a result of the blended learning model, and there is no interaction of the influence of the application of learning model and motivation to student achievement.